Pengembangan Modul Pembelajaran Kriya Tekstil Berbasis PjBL Pada Jurusan PKK FT UNM - Kurniati; Asiani Abu; Irmayanti (SEMINAR NASIONAL DIES NATALIS 62, 2023)
This research aims to understand and comprehend the procedures involved in the development of a Project Based Learning-based Textile Crafts learning module. It also aims to analyze the feasibility of the learning module in the Textile Crafts course to enhance student learning outcomes. The development procedure follows the ADDIE model, which consists of five main steps: Analysis, Design, Development, Implementation, and Evaluation. The research results indicate that: (1) the developed learning module for the Textile Crafts course is categorized as valid, and (2) the students response to the learning module yields positive feedback. Therefore, it can be concluded that the developed Project Based Learning-based Textile Crafts module is suitable for use as teaching material in the Textile Crafts course at the Department of Home Economics Education, Faculty of Engineering, Universitas Negeri Makassar.